1977
DOI: 10.1007/bf00312946
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and chemical study of calcification of the choroid plexus

Abstract: Human choroid plexus was submitted to low temperature ashing (LTA) in order to isolate the calcification. The ashing residue was then subjected to morphological, chemical and structural studies using technics such as scanning electron microscopy, flame and flameless atomic absorption spectrometry, infrared spectrometry and X-ray diffraction. Morphologically, the calcification consisted of wound-up fibers forming granules with a diameter of 0.05 to 0.15 mm. The concretions were identified as cristalline Ca3(PO4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…By an improved histochemical staining method, a substantial staining of iron can be seen in neuroglial cells and in the choroid plexus epithelial cells (Moos and Mollgard, 1993). In human subjects with a calcified choroid plexus, iron concentration in the choroid plexus was about 5 times greater than the values obtained from other brain tissues (Michotte et al, 1977).…”
Section: Sequestered Choroid Plexus Toxicants Iron (Fe)contrasting
confidence: 57%
See 1 more Smart Citation
“…By an improved histochemical staining method, a substantial staining of iron can be seen in neuroglial cells and in the choroid plexus epithelial cells (Moos and Mollgard, 1993). In human subjects with a calcified choroid plexus, iron concentration in the choroid plexus was about 5 times greater than the values obtained from other brain tissues (Michotte et al, 1977).…”
Section: Sequestered Choroid Plexus Toxicants Iron (Fe)contrasting
confidence: 57%
“…There is no direct evidence toward manganese-associated damages in cerebral microvascular structure, nor can it be found about structural injury resulting from manganese toxicity in choroidal epithelial cells. However, manganese indeed accumulates in the choroid plexus (Ingersoll et al, 1995;Michotte et al, 1977;Valois and Webster, 1989b;Zheng et al, 1998b). The influx constant of manganese to the choroid plexus was about 150 and 1,000 times greater than that of cerebral cortex and CSF, respectively, when the plasma manganese was maintained at a constant level (Murphy et al, 1991).…”
Section: Manganese In Choroid Plexus and Csf Upon Exposurementioning
confidence: 99%
“…Ferric iron was detected by the Perl's technique in psammoma bodies in the choroid plexus but not by EDAX. Nevertheless, support for the presence of iron comes from spectroscopic analysis by Michotte et al (1977b). They showed that iron was present in the choroid plexus at a concentration above that found in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…With histochemical staining, a substantial amount of Fe can be seen in neuroglial cells and in the choroid plexus epithelial cells (Moos and Mollgard, 1993). In human subjects with a calcified choroid plexus, Fe concentration in the choroid plexus is about five times greater than in other brain tissues (Michotte et al, 1977).…”
Section: Ironmentioning
confidence: 99%
“…There is no experimental evidence in support of Mn-induced direct damage to cerebral microvascular structure nor is much known about structural injury as a direct result of Mn toxicity in choroidal epithelial cells. Mn, however, readily accumulates in the choroid plexus (Michotte et al, 1977;Valois and Webster, 1989;Zheng et al, 1998). The influx of Mn to the choroid plexus is about 150 and 1000 times greater than that of cerebral cortex and CSF, respectively, when the plasma concentration of the infused Mn is maintained constantly (Murphy et al, 1991).…”
Section: Manganesementioning
confidence: 99%